STUDIES ON ACUTE TOXICITY OF HEPTOPLUS IN EXPERIMENTAL RATS - Sankar, M.; Rajkumar, Johanna (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To evaluate acute toxicity of Heptoplus (polyherbal drug) in Sprague-Dawley rats and to identify the active ingredients of the herbal drug. Methods: Heptoplus was subjected to preliminary phytochemical screening and the HPTLC fingerprint profile of herbal drug was documented. OECD guideline 423-Acute toxic class method was followed to evaluate the oral toxicity of Heptoplus in Sprague-Dawley rats. In acute toxicity studies, Group I (control) rats received 0.5% of carboxymethyl cellouse (Vehicle). Group II rats received 2000 mg/kg b. w of Heptoplus. The rats were observed on the day of dosing and thereafter for 14 d, for any toxic effect. Results: Preliminary phytochemical analysis of Heptoplus revealed total phenol, flavonoid, carbohydrate, and tannins as its major constituents. The total phenol and flavonoid content of Heptoplus was found to be 170 Î¼g of gallic acid and 162 Î¼g of quercetin equivalent. HPTLC analysis proved that phyllanthin is an active compound of Heptoplus. Acute oral toxicity assays showed Heptoplus administration did not result in any treatment-related mortality, abnormal clinical signs, and loss of body weight or gross pathological changes in rats. Hence, LD50 value of Heptoplus was found to be greater than 2000 mg/kg b. wt. Conclusion: Heptoplus contain phyllanthin as an active ingredient. LD50 value of Heptoplus was found to be greater than 2000 mg/kg b. wt.